Combined use of NK cells and radiotherapy in the treatment of solid tumors - Zheng, Wang; Ling, Sunkai; Cao, Yuandong; Shao, Chunlin; Sun, Xinchen (Frontiers in Immunology, 2024)
Natural killer (NK) cells are innate lymphocytes possessing potent tumor surveillance and elimination activity. Increasing attention is being focused on the role of NK cells in integral antitumor strategies (especially immunotherapy). Of note, therapeutic efficacy is considerable dependent on two parameters: the infiltration and cytotoxicity of NK cells in tumor microenvironment (TME), both of which are impaired by several obstacles (e.g., chemokines, hypoxia). Strategies to overcome such barriers are needed. Radiotherapy is a conventional modality employed to cure solid tumors. Recent studies suggest that radiotherapy not only damages tumor cells directly, but also enhances tumor recognition by immune cells through altering molecular expression of tumor or immune cells via the in situ or abscopal effect. Thus, radiotherapy may rebuild a NK cells-favored TME, and thus provide a cost-effective approach to improve the infiltration of NK cells into solid tumors, as well as elevate immune-activity. Moreover, the radioresistance of tumor always hampers the response to radiotherapy. Noteworthy, the puissant cytotoxic activity of NK cells not only kills tumor cells directly, but also increases the response of tumors to radiation via activating several radiosensitization pathways. Herein, we review the mechanisms by which NK cells and radiotherapy mutually promote their killing function against solid malignancies. We also discuss potential strategies harnessing such features in combined anticancer care.